On the persistence of trade imbalances: Evidence from Europe - Helge Berger; Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2013)
Does exchange rate variability affect the speed of external adjustment? We study bilateral trade balances for a sample of 18 European countries over the period from 1948 through 2008. We find that, with the introduction of the euro, trade imbalances among euro area members widened considerably, even after allowing for permanent asymmetries in trade competitiveness within pairs of countries or in the overall trade competitiveness of individual countries. Intra-euro area imbalances also seem to have become more persistent with the introduction of the euro. Greater persistence is partially linked to economic and regulatory inflexibilities, such as fiscal restrictions and labor market rigidities.
Keywords: F15; F16; F32; F36; F42; 330; imbalances; trade balance; trade surplus; trade deficit; persistence; euro; EMU; European integration